Organizational and pedagogical conditions of formation of teacher’s professional image in the context of education standartization - Ekaterina V. Sharueva (Вестник Самарского государственного технического университета. Серия: Психолого-педагогические науки)
In the structure of modern standards of education, one of the important and popular components that increases the effectiveness of pedagogical activity is the professional image of the teacher. The importance of teachers professional image formation is actualized as this image promotes not only productivity, but also influences the perception of the teaching work representative by participants of the educational process. In the process of teachers professional image formation organizational and pedagogical conditions should be provided considering the context of standardization of education. The concept of the conditions in question is defined. The analysis of theoretical research of pedagogical conditions of teachers professional image formation is based on the requirements to pedagogical activity of Federal state educational standards and the professional standard Teacher, which allowed to determine current organizational and pedagogical conditions of the teachers professional image formation in terms of standardization of education. The objective organizational conditions for teachers professional image formation are the following: standardization of the education process, creation of a polysubject educational environment, teachers motivation formation for professional and image development, the development of professional and image competence of teachers, the development of image self-reflection in the professional activities of teachers.